Health Dialogue Elements Identified during Health Communication between Nurses and Patients. - Talbot, Lesley; Nel, Mariette; Reid, Marianne (Africa Journal of Nursing & Midwifery, 2020)
Nurse-patient communication is an essential component of patient-centred health care that improves health outcomes and is characterised by health dialogue sanctioning mutual participation of both parties. This article reports on a study that aimed to identify the use of health dialogue elements during nurse-patient communication. A quantitative, descriptive, cross-sectional research design was used. The data was collected using the Observational Checklist of Health Dialogue Elements (OCHDE). The population comprised nurses (N=89) and adult diabetic patients in their care in a local municipality in Northern Cape, South Africa. Proportional sampling of public and private health facilities (n=16) was followed by convenience sampling of nurses (n=22). Descriptive statistics were calculated per group, comparing the nurse and patient responses per health dialogue element. The use of health dialogue elements during nurse-patient communication was diverse with an inconsistent display of antecedents, namely, a positive attitude (71.4%) and sensitivity and respect (41.7%) during communication. Regarding the antecedent element, training, the nurses displayed inadequate training in diabetes (19.3%) and in communication skills (30.6%). The patients received more diabetes training (48.7%) than the nurses, but their communication skills training (3.4%) was low. However, both the nurses and patients perceived the empirical referents, namely, shared responsibility/decision-making (67%, 68.2%), a health plan of mutual benefit (79.5%, 81.6%), and the use of context-sensitive communication strategies (73.6%, 67.8%). The inconsistent presence of antecedents and the reported presence of empirical referents indicates a need for further research and capacity building of nurses and patients.